Using Environmental Information to Engage Public Participation in Decision Making in Coastal Policy Development - Soomai, Suzuette S.; MacDonald, Bertrum H.; Wells, Peter G. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper presents findings of a study of the awareness and use of The 2009 State of Nova Scotia’s Coast Report by specific stakeholder groups and the general public. Communication of the Report to wider audiences was identified as a main issue in increasing public participation in the development of provincial coastal policy. Cet article présente les résultats d’une étude sur le niveau de connaissance et l’utilisation du 2009 State of Nova Scotia’s Coast Report par des groupes d’intervenants précis ainsi que par le grand public. On a identifié la communication du rapport à un vaste auditoire comment étant le principal moyen pour augmenter la participation publique dans le développement d’une politique côtière provinciale.